Proteomic Analysis Reveals Key Proteins and Phosphoproteins upon Seed Germination of Wheat (Triticum aestivum L.) - Dong, Kun; Zhen, Shoumin; Cheng, Zhiwei; Cao, Hui; Ge, Pei; Yan, Yueming (Frontiers in Plant Science, 2015)
Wheat (Triticum aestivum L.) is one of the oldest cultivated crops and the second most important food crop in the world. Seed germination is the key developmental process in plant growth and development, and poor germination directly affects plant growth and subsequent grain yield. In this study, we performed the first dynamic proteome analysis of wheat seed germination using a two-dimensional differential gel electrophoresis (2D-DIGE)-based proteomic approach. A total of 166 differentially expressed protein (DEP) spots representing 73 unique proteins were identified, which are mainly involved in storage, stress/defense/detoxification, carbohydrate metabolism, photosynthesis, cell metabolism, and transcription/translation/ transposition. The identified DEPs and their dynamic expression profiles generally correspond to three distinct seed germination phases after imbibition: storage degradation, physiological processes/morphogenesis, and photosynthesis. Some key DEPs involved in storage substance degradation and plant defense mechanisms, such as globulin 3, sucrose synthase type I, serpin, beta-amylase, and plastid ADP-glucose pyrophosphorylase (AGPase) small subunit, were found to be phosphorylated during seed germination. Particularly, the phosphorylation site Ser355 was found to be located in the enzyme active region of beta-amylase, which promotes substrate binding. Phosphorylated modification of several proteins could promote storage substance degradation and environmental stress defense during seed germination. The central metabolic pathways involved in wheat seed germination are proposed herein, providing new insights into the molecular mechanisms of cereal seed germination.